2018
DOI: 10.3390/f9110681
|View full text |Cite
|
Sign up to set email alerts
|

How Does Leaf Surface Micromorphology of Different Trees Impact Their Ability to Capture Particulate Matter?

Abstract: Particulate matter (PM), including PM10 and PM2.5, has a major impact on air quality and public health. It has been shown that trees can capture PM and improve air quality. In this study, we used two-way ANOVA to investigate the significance of micro-morphological leaf surface characteristics of green trees in capturing PM at different parks in Beijing. The results show that leaf structure significantly impacts the ability of plants to capture PM. Pinus tabuliformis Carr. and Pinus bungeana Zucc. were mainly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 32 publications
(38 reference statements)
2
17
0
2
Order By: Relevance
“…However, Zhang et al 111 observed a difference in significance of individual features between broadleaved and coniferous species: increased leaf micro-roughness (characterised by grooves and ridges on the leaf surface) was found to correlate with increased deposition to broadleaves, whereas stomatal density and amount of epicuticular wax were found to positively correlate with deposition to coniferous (needle) leaves. These findings were corroborated by a similar, subsequent study 112 .…”
Section: Leaf Surface Featuressupporting
confidence: 78%
See 2 more Smart Citations
“…However, Zhang et al 111 observed a difference in significance of individual features between broadleaved and coniferous species: increased leaf micro-roughness (characterised by grooves and ridges on the leaf surface) was found to correlate with increased deposition to broadleaves, whereas stomatal density and amount of epicuticular wax were found to positively correlate with deposition to coniferous (needle) leaves. These findings were corroborated by a similar, subsequent study 112 .…”
Section: Leaf Surface Featuressupporting
confidence: 78%
“…for individual pollutant types is currently unclear and an area for further research 118 . However, it may be generalised that rough leaf surfaces (including grooves, ridges and trichomes) are more beneficial than smooth surfaces for particle deposition, that epicuticular wax is beneficial (particularly for deposition to conifers 111,112 ) and that stomatal traits play a significant role that warrants further investigation. These points conform to different processes outlined in Supplementary Section S1, which highlights that different surface features will vary in influence for different target pollutants.…”
Section: Leaf Surface Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant level study [10][11][12][13][31][32][33][35][36][37][38][39][40][41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]65,69,73] Local scale [14][15][16][17]19,[21][22][23][24][26][27][28][29]34,44,63,75,76] Neighbourhood scale [18,…”
Section: Scale Referencementioning
confidence: 99%
“…The capacity of plants to check air pollution is well recognized and cited in the standard literature on numerous occasions [2][3][4][5]. Foliar uptake [5][6][7] of metal and metalloid particulates is reported by many authors [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%